(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Being natural method, breast crawl is initiated by instinctive nature of human behavior, where babies use sucking behavior when allowed to do so. As soon as the baby is place on abdomen of the mother soon after the birth, new born starts searching for mother’s breast on its own. This study is carried out to assess the proportion of breast crawl. Material and Method: 371 mothers who delivered at full term without any complications were involved in the study. Check list was used for assessing the successful and unsuccessful breast crawl. Results: Out of 371 babies, 344 (93%) babies have succeeded in the breast crawl. 248 (67%) babies crawled without any assistant, 80 (22%) babies crawled with partial assistant and only 16 (4%) babies Baby crawled and took feed with full assistance. Conclusion: The success rate of the breast crawl in this study was 93% which indicates these techniques of breast crawl can be practiced in every maternity setting. The study concludes that breast crawl is a simple and cost effective method for fetal positive adaptation to the environment.